Theoretical studies of dimers and properties of the corrosion inhibitor profile for semicarbazones and thiosemicarbazones - Silva, Ámison Rick L.; Martínez-Huitle, Carlos A. [UNESP] (Elsevier, 2021)
Specific molecular properties have been theoretically and experimentally evaluated for selecting a corrosion inhibitor. In the theoretical case, for example, the ability to donate electrons, which is related to the frontier orbitals and their ionization potential as well as its electronic affinity, have been widely studied. However, other molecular properties could be also evaluated in order to determine the effectiveness of corrosion inhibitor. In this frame, the adsorption capacity on the metallic surface by the inhibitor can be also theoretically evaluated in order to understand the self-assembly monolayer (dimers formed by the inhibitor), which acts as a barrier that decreases the kinetics of the metallic corrosion process. Electronic descriptors using three functionals B3LYP, BHandLYP and BLYP showed good correlations with experimental data. Starting from the best results of the correlations, dimer structures were studied and evaluated on their influence on the corrosion inhibiting ability. Thus, the proposal indicated possible forms of film formation and possible stronger interactions that influence film formation. This new approach of studies using dimers to evaluate the inhibitor profile of the molecule, revealed to be a promising proposal for computational protocols for studies of corrosion inhibitors.
Keywords: Corrosion; DFT; Dimers and QTAIM; Semicarbazones; Thiosemicarbazones